2019
DOI: 10.1002/bmb.21293
|View full text |Cite
|
Sign up to set email alerts
|

Social‐media use and academic performance among undergraduates in biology

Abstract: The development of social media applications has made it an important part of students' personal lives. In this article, we aim to determine whether social media usage is beneficial or harmful to college students through academic performance. Through a survey of biological undergraduates, we found that boys use social media applications more frequently than girls, and that GPA is inversely related to the number of social media applications that students subscribe to. In addition, we found that using more socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…An alternative explanation for this phenomenon may be related to the use of social applications that students use to connect with their friends. The increase in the number of hours students spend on social media has a negative impact on study habits and academic performance [ 37 , 38 ]. Therefore, social support from friends may interfere with academic performance if students spend too much time on social networks and neglect their academic responsibilities, rather than building social support relationships, which is a predictor of good academic performance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for this phenomenon may be related to the use of social applications that students use to connect with their friends. The increase in the number of hours students spend on social media has a negative impact on study habits and academic performance [ 37 , 38 ]. Therefore, social support from friends may interfere with academic performance if students spend too much time on social networks and neglect their academic responsibilities, rather than building social support relationships, which is a predictor of good academic performance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dalam membahas variabel diatas dengan mempertimbangkan hasil penelitian sebelumnya yang telah melaporkan hubungan negatif antara penggunaan media sosial dan prestasi akademik, yang diukur dengan IPK yang dilaporkan sendiri dan jam yang dihabiskan untuk belajar per minggu (Shen, J., 2019). Penelitian tersebut juga akan mempertimbangkan hasil studi yang dilakukan oleh Weidinger, L., dkk.…”
Section: Prestasi Akademikunclassified
“…Some scholars also applied this instrument to conduct their study in adolescent samples, the results demonstrated that males were more likely to be addicted in social media (Altin and Kivrak, 2018 ; Azizi et al, 2019 ; Shibli and Akhtar, 2020 ; Luo et al, 2021 ; Gao and Eissenstat, 2022 ). In these scholars' opinion, men may experience more negative effects and be more likely to have a poor academic performance, which will lead men to use social media for longer time as opposed to their female counterparts and contribute to their vulnerability of social media addiction (Shen, 2019 ; Bhandarkar et al, 2021 ; Gao and Eissenstat, 2022 ). Moreover, some studies also contended that there was no significant association between gender and the severity of social media addiction (Kirik et al, 2015 ; Ahmed et al, 2021 ; Cheng, 2021 ; Mahmood et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%